The Application of the RADEC Model with Nearpod Media in Enhancing Cultural and Citizenship Literacy : Penerapan Model RADEC dengan Media Nearpod dalam Meningkatkan Literasi Budaya dan Kewarganegaraan - Lestari, Hana; Rahmawati, Ima (UIN Raden Mas Said Surakarta, 2025)
This study aims to examine the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model integrated with Nearpod media in enhancing elementary students’ cultural and citizenship literacy. The research involved 60 students from two public elementary schools using a quantitative pre-experimental design with a one-group pre-test and post-test approach. The results showed an increase in students’ average scores from 59.5 (pre-test) to 83.5 (post-test), with a t-test significance value of 0.01 (p < 0.05), indicating a statistically significant improvement. Each literacy indicator cultural understanding, civic awareness, responsibility, and participation demonstrated consistent growth throughout each stage of the RADEC model. The learning process, supported by interactive Nearpod features such as quizzes, polls, collaboration boards, and digital projects, encouraged students to actively engage, internalize cultural and citizenship values, and express their understanding creatively. Observation results showed an average implementation rate of 85.41%, categorized as “very good.” These findings confirm that integrating the RADEC model with Nearpod media not only improves student learning outcomes but also fosters meaningful engagement with cultural and civic issues, making it a valuable approach for broader educational application.